2017
DOI: 10.5152/npa.2017.12707
|View full text |Cite
|
Sign up to set email alerts
|

Examination of Psychometric Properties of the Need for Closure Scale- Short Form among Turkish College Students

Abstract: The need for cognitive closure (NFC) has recently gained importance in behavioral neuroscience. In recent years, the impact of motivation in social psychology and personality psychology on cognition has begun to be examined, and the need for cognitive closure was explained by a detailed theory (1). The Theory of Daily Scientificism (Epistemology) put forward by Kruglanski and Ajzen (2) examines how individuals constitute their knowledge in everyday life, how they change this knowledge, and in what ways they ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
0
3
0
1
Order By: Relevance
“…NFC showed a positive correlation with right‐wing authoritarianism and blatant racism and a negative correlation with openness to experience (Roets & Van Hiel, 2011). Atak et al (2017) also reported internal consistency of 0.74. In this study, the scale showed good internal consistency of 0.76 as measured by Cronbach's α .…”
Section: Methodsmentioning
confidence: 95%
See 1 more Smart Citation
“…NFC showed a positive correlation with right‐wing authoritarianism and blatant racism and a negative correlation with openness to experience (Roets & Van Hiel, 2011). Atak et al (2017) also reported internal consistency of 0.74. In this study, the scale showed good internal consistency of 0.76 as measured by Cronbach's α .…”
Section: Methodsmentioning
confidence: 95%
“…correlation with right-wing authoritarianism and blatant racism and a negative correlation with openness to experience (Roets & Van Hiel, 2011). Atak et al (2017) also reported internal consistency of 0.74. In this study, the scale showed good internal consistency of 0.76 as measured by Cronbach's α. Confirmatory factor analysis (CFA) in this study also yielded good fit indices χ 2 /df = 4.09, CFI = 0.96, RMSEA = 0.05, SRMR = 0.04.…”
Section: Instrumentsmentioning
confidence: 96%
“…Epistemic motivation involves the eagerness to participate in deep thinking (Scholten et al, 2007) and is autonomously constructed to make educated assumptions about the world (de Dreu et al, 2008). Epistemic motivation originally consisted of the need for cognition and the need for closure (Atak et al, 2017). The need for cognition deals with how individuals differ in terms of cognitive motivation, information processing (Dickhäuser et al, 2009), their ability to remember complex information, and make precise judgments after careful deliberation of available information tasks (Cacioppo et al, 1984).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Proto Roets a Van Hiel (2011) zkonstruovali krátkou verzi NFCS s 15 položkami (dále NFCS-15), která byla posléze validována v dalších jazycích, např. španělštině (Horcajo et al, 2011) či turečtině (Atak, Syed, & Çok, 2017). Českou 3 validaci (NFCS-15-CZ) provedli Širůček a spolupracovníci na celkovém vzorku více než 2500 respondentů ve věku 16 až 43 let (Širůček et al, 2014;Širůček & Ježek, 2015).…”
Section: Měření Potřeby Kognitivního Uzavřeníunclassified